Strain-Induced Precipitation Kinetics of Vanadium Carbonitride Precipitates with the Cubic Structure in High-Strength Weathering Steels - Cheng, J.; Qing, J.; Shen, H.F. (Проблемы прочности, 2018)
The strain-induced precipitation kinetic model of vanadium carbonitride [V(C, N)] precipitates with the cubic structure in vanadium-nitrogen (V–N) microalloyed high-strength weathering steels was constructed and validated.